STRATEGI REKRUTMEN DAN SELEKSI CALON SISWA BARU DALAM MENINGKATKAN MUTU LEMBAGA PENDIDIKAN MADRASAH ALIYAH NEGERI 1 MEDAN T.P 2020/2021 - Ramadhany, Dinda; Daulay, Nurika Khalila; Fauza, Hendri (Universitas Islam Negeri Sumatera Utara Medan, 2021)
In general, this study aims to describe (1) the recruitment process used by MAN 1 Medan in the acceptance of new prospective students in (2) the selection process used by MAN 1 Medan in the acceptance of new students (3) the obstacles faced in the recruitment process and selection of prospective new students at MAN 1 Medan (4) efforts made so that the process of recruiting and selecting prospective new students runs effectively and efficiently at MAN 1 Medan. This study uses qualitative research with a phenomenological method approach. The subjects of this study were the Principal, members of the PPDB committee and Student WKM. Data collection techniques by observation, interviews and documentation. The data analysis technique uses the Miles and Huberman model. Data validity techniques with credibility, transferability, dependability and confirmability. The results of the study show the following: (1) The recruitment and selection process includes the formation of a committee, notification of information regarding PPDB has been opened through banners, brochures etc., online registration by attaching the specified files, announcement of file selection, selection of academic tests, selection of Al reading tests -Qur'an and worship practices, announcement of selection graduation, and re-registration. (2) the selection process used includes file selection, academic test selection and selection of tests for reading the Qur'an and worship practices (3) the obstacles that occur during the recruitment and selection process using the online system do not have a big impact. Only small obstacles can then be overcome by the school. (4) The efforts made by the school can minimize obstacles and make the implementation of recruitment and selection run effectively and efficiently. Based on the research, it can be concluded that the recruitment and selection strategy used by Madrasah Aliyah Negeri 1 Medan in T.P 2019/2020 is file registration, then academic test selection and selection of Al-Qur'an reading tests and worship practices using the online system as a whole in the process.Recruitment and Selection Strategy, New Students, Quality of Education